2006
DOI: 10.1007/s11064-006-9040-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of N-acetylcysteine on Experimental Closed Head Trauma in Rats

Abstract: N-acetylcysteine (NAC) is a precursor of glutathione, a potent antioxidant, and a free radical scavenger. The beneficial effect of NAC on nervous system ischemia and ischemia/reperfusion models has been well documented. However, the effect of NAC on nervous system trauma remains less understood. Therefore, we aimed to investigate the therapeutic efficacy of NAC with an experimental closed head trauma model in rats. Thirty-six adult male Sprague-Dawley rats were randomly divided into three groups of 12 rats eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 59 publications
4
49
0
6
Order By: Relevance
“…In this study, closed head trauma caused severe degenerative changes, shrunken cytoplasma and extensively dark picnotic nuclei in neurons of the frontal cortex tissues. This observation is in agreement with previous studies, which suggest that closed head trauma caused severe degenerative changes in neurons of frontal cortex and NAC treatment prevented this neuronal damage (Hicdonmez et al, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, closed head trauma caused severe degenerative changes, shrunken cytoplasma and extensively dark picnotic nuclei in neurons of the frontal cortex tissues. This observation is in agreement with previous studies, which suggest that closed head trauma caused severe degenerative changes in neurons of frontal cortex and NAC treatment prevented this neuronal damage (Hicdonmez et al, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…They reported favorable effects of NAC treatment on the oxidative brain tissue injury induced by the trauma. 27 However, in a study on rats with moderate left focal cortical contusion trauma, Thomale et al found that 163 mg/kg of NAC applied intraperitoneally 2-4 h after the brain injury was ineffective against post-traumatic perfusion, brain edema or contusion volume. 28 Cuzzocrea et al investigated the effect of NAC on brain ischemic injury in gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine has been shown to have anti-inlammatory and antioxidant actions, increasing glutathione synthesis to scavenge ROS, decreasing IL-1β and TNF-α levels in brain injury, decreasing caspase-3 levels, and shifting microglia towards M2 anti-inlammatory phenotypes [268][269][270][271].…”
Section: N-acetylcysteinementioning
confidence: 99%